Ask Question
3 April, 14:43

If p (x) = x2 - 1 and q (x) = 5 (x minus 1), which expression is equivalent to (p - q) (x) ?

0
Answers (2)
  1. 3 April, 15:06
    0
    Step-by-step explanation:

    P (x) = x² - 1 and Q (x) = 5 (x - 1)

    (P - Q) (x) = x² - 1 - 5 (x - 1)

    = x² - 1 - 5x + 5

    = x² - 5x + 4
  2. 3 April, 16:22
    0
    All you need to do p (x) - q (x). So:

    (x^{2}-1) - (5) (x-1)

    That's it!
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “If p (x) = x2 - 1 and q (x) = 5 (x minus 1), which expression is equivalent to (p - q) (x) ? ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers